Impact of bitter taste receptor phenotype upon clinical presentation in chronic rhinosinusitis. Issue 9 (4th July 2018) - Rowan, Nicholas R.; Soler, Zachary M.; Othieno, Florence; Storck, Kristina A.; Smith, Timothy L.; Schlosser, Rodney J.
Abstract : Background: Genetic variation of the bitter taste receptor T2R38 has been associated with recalcitrant chronic rhinosinusitis (CRS). Specific T2R38 polymorphisms, correlating with bitter taste sensitivity to phenylthiocarbamide (PTC), have been identified as an independent risk factor for surgical intervention in CRS patients without polyps; however, the exact role of PTC tasting ability in clinical practice remains unknown. In this investigation we characterize PTC taste sensitivity in a tertiary care rhinology practice with pertinent clinical measures of disease and quality of life (QOL). Methods: Adult CRS patients were prospectively assessed for their ability to taste PTC and categorized as nontasters, tasters, or supertasters. Objective taste was assessed with strips for bitter, sweet, sour, and salty, whereas olfactory testing was measured with Sniffin' Sticks. Correlation was performed between PTC tasting ability and patient demographics, endoscopy scores, validated QOL surveys, and both subjective and objective measures of taste and olfaction. Results: Sixty‐seven patients were enrolled. Fifty‐two percent were identified as nontasters, 34% as tasters, and 13% as supertasters. Nontasters were more likely to be non‐Hispanic ( p = 0.018), white ( p = 0.027), without nasal polyposis ( p = 0.004), and nonasthmatics ( p = 0.019). There were no other statistical differences in patients' demographics, QOL measures, and subjective or objective olfactory and taste scores when compared with patients' oral PTC‐sensing ability. Conclusion: Oral PTC‐sensing ability may serve as a convenient marker of increased disease severity in white CRS patients without polyps and vary among regional populations. PTC tasting ability appears to provide unique phenotypic information not obtained using other subjective or objective measures of smell and taste.